Utilizing Wearable Technologies to Foster Outcome-Based Education in Learning Factories - Sofiyan; Lucas Lawrence; Lily Maria Evans; Khaizure Mirdad; Chen Yu (Pandawan Sejahtera Indonesia, 2025)
The integration of wearable technologies into educational settings has opened new avenues for enhancing experiential and outcome-based learning, particularly in practice-oriented environments such as learning factories. This study investigates how wearable devices such as smart glasses, biometric trackers, and haptic feedback systems can be effectively utilized to support real-time performance monitoring, contextual learning, and continuous skill assessment in engineering and manufacturing training. The objective of this research is to explore the potential of these technologies in reinforcing the principles of outcome-based education (OBE), where learner competence is measured through demonstrable performance rather than passive knowledge acquisition. A mixed-method approach was adopted, combining qualitative field observations and interviews with quantitative data collected through controlled experiments involving wearable technology use in a simulated learning factory environment. The findings reveal that wearables significantly contribute to increased learner engagement, improved task efficiency, and enhanced feedback mechanisms, leading to better alignment between learning outcomes and industrial competency demands. Moreover, the results suggest that wearable-assisted learning environments foster reflective learning and support personalized instruction by capturing granular data on learner behaviors and outcomes. This research concludes that integrating wearable technologies into learning factories not only enhances the quality and relevance of vocational and technical education but also supports broader sustainable development goals by promoting inclusive, adaptive, and technologically enriched learning systems. The study provides a foundation for future research into scalable, data-driven educational models and the role of emerging technologies in transforming skill-based education.